Excavations at Newtonferry (Scottish Historical and Archaeological Internet Reports, 2003)
Details of site location, previous work and site history are presented. Nearby sites include cist burials, standing stones, a possible earth house, a Norse burial cairn and a local tradition of a settlement. Excavation revealed midden deposits, windblown sands and a stone setting of medieval or post-medieval date.